REGULASI DAN IMPLEMENTASI PENDIDIKAN INFORMAL - Hatimah, Ihat (PEDAGOGIA, 2015)
Regulation of informal education stipulated in the Law on National Education System No. 20 of 2003 Article 27, namely: 1) informal education activities carried out bythe family and the environment in the form of learning activities independently, 2) Results of education referred to in subsection (1) is recognized equal to formal and informal education after students pass the exam in accordance with national standards of education, 3) provisions regarding the admission of informal education as referred to in paragraph (2) shall be regulated further by a government regulation. Implementation ofinformal education the most obvious is through the family, because the family is the lead agency and the first for children's development. Parents should be able to be a parent of intelligent loving that can be realized in the form of: 1) facilitating children to grow and be happy, 2) train independence, 3) instilling confidence, 4) help facilitate reading books that are useful, 5) invite children to play wholeheartedly, 6) facilitates to communicate, solve problems, make decisions, 7) invites move or move, 8) guiding when watching television.Keywords: regulation, informal education, informal education implementation